A STUDY TO COMPARE EFFICACY OF DISINFECTANTS AGAINST STAPHYLOCOCCUS AUREUS IN UNIVERSITI SAINS ISLAM MALAYSIA - Martina Winarti, Tine; Azmawati Mohamed, Nurul; Amirah Ab Aziz, Nur; A’mirah Ahmad Lotfi, Nurul (Journal of Health and Dental Sciences, 2024)
Different levels of active ingredients in disinfectants can be classified into three levels of disinfectants. Low-level and low-to-intermediate level disinfectants are commonly used in clinical contact surfaces, while high-level disinfectants are used on submerged inanimate objects that are heat sensitive. This study aimed to compare the disinfection efficacy of different disinfectants used in USIM Dental Polyclinic on rough and smooth surfaces against Staphylococcus aureusisolated from USIM Dental Polyclinic. 19 operators were enrolled to get 19 environmentalsamples from the glove-dominant hand after non-surgical extraction in the Oral Surgery Clinic. Staphylococcus aureus wasidentified, and an antibiotic susceptibility test was done to determine the methicillin-resistant Staphylococcus aureus(MRSA) strain. Two different levels of disinfectants for the disinfection of dental chairs were tested on rough and smooth surfaces that were contaminated experimentally by Staphylococcus aureus. The number of colonies without and after disinfection was counted, and the reduction percentagewas calculated and analyzed.Staphylococcus aureuswas detected in 68.42% (n=13) of the samples. 5.26% (n=1) of the samples were Staphylococcus sp. 26.32% (n=5) had no bacterial growth. No methicillin-resistant Staphylococcus aureusstrain was identified. There was no statistically significant difference (p>0.05) between the efficacy of the three disinfectants from two different levels used in USIM Dental Polyclinic on rough and smooth surfaces against Staphylococcus aureus. Theefficacy of different levels of disinfectants used in USIM Dental Polyclinic was comparable to each other on rough and smooth surfaces against Staphylococcus aureus DOI : 10.54052/jhds.v3n3.p333-344